The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10620-011-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Enterally Delivered Angiotensin II Type Ia Receptor Antagonists to Reduce the Severity of Colitis

Abstract: Background Renin-angiotensin system blockade reduces inflammation in several organ systems. Having found a fourfold increase in angiotensin II type Ia receptor expression in a dextran sodium sulfate colitis model, we targeted blockade with angiotensin II type Ia receptor antagonists to prevent colitis development. Because hypotension is a major complication of angiotensin II type Ia receptor antagonists use, we hypothesized that use of angiotensin II type Ia receptor antagonists compounds which lack cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Inflammatory cytokines were then measured as a marker of the pro-inflammatory response in this colitis model [26]. As a trend, drug treatment led to a reduction in the abundance of several of the pro-inflammatory cytokines and chemokine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines were then measured as a marker of the pro-inflammatory response in this colitis model [26]. As a trend, drug treatment led to a reduction in the abundance of several of the pro-inflammatory cytokines and chemokine.…”
Section: Resultsmentioning
confidence: 99%
“…Although several authors have used the DSS colitis model to investigate Renin-Angiotensin System (RAS) blockade and colitis [26, 3336], the data presented here are the first which demonstrate RAS blockade efficacy using an immune-based model. In the present study we utilized an IL-10−/− colitis immune-based model and demonstrated that ACE-I treatment was as good, or far superior, to that of conventional steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the latter, IBD patients have been found to produce higher than normal levels of angiotensin II (Jaszewski et al, 1990), with experimentally-induced colitis alleviated in angiotensinogen knockout mice (Inokuchi et al, 2005) and also attenuated by inhibition with the angiotensin II receptor antagonists losartan and candesartan (Inokuchi et al, 2005; Okawada et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Its family includes extracellular signal-related kinases, c-Jun N-terminal kinases and p38 (32). A recent study demonstrated that high levels of glucose-protein kinase C pathways, glycation end products, oxidative stress, growth factor, osmotic pressure and stretches under diabetic conditions may activate MAPK families, increase the activity of transcription factors and lead to chronic diabetic complications (33).…”
Section: Discussionmentioning
confidence: 99%